Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Promosi Terhadap Kepuasan Pengunjung Di Wahana Permainan Trans Studio Cibubur - Wahyuningsih, Siti; Wasino, Wasino (Universitas Pahlawan Tuanku Tambusai, 2024)
The more recreational businesses that operate, the higher the level of competition. Every leisure tourism tourism must remain aware of the changes taking place in the market and be able to develop innovative ideas to make the goods and services they offer demand the interest of visitors, so that what visitors need can be met and the company is able to face the competition. This study aims to analyze the relationship between service quality, price perception and promotion on visitor satisfaction at Trans Studio Cibubur. In this study using descriptive quantitative methods. The population or respondents of this survey are all customers who visited Trans Studio Cibubur more than twice. Researchers chose the purposive sampling method by determining specific characteristics to be used as respondents, totaling 130 people. Based on the results of this study, it can be seen that service quality, price perception and promotion have a positive and significant effect on visitor satisfaction at Trans Studio Cibubur